(untitled) (E Conference Zone, 2022)
The first problem Enkvist (1990) outlines is the difficulty of defining the relation between cohesion and coherence. He maintains that the positivist approach traditionally followed by linguists which has encouraged a focus on "concretely describable entities" ( 1990: 11) has meant that text linguists and discourse analysts have tended to focus on formal cohesive relations as evidence of what combines sentences into texts.